Radical sensitivity and selectivity in the electrochemical sensing of cadmium ions in water by polyaniline-derived nitrogen-doped graphene quantum dots. (9th December 2020) - Saisree, S.; Aswathi, R.; Arya Nair, J. S.; Sandhya, K. Y.
Abstract : In the present work, the sensing capability of nitrogen-doped graphene quantum dots (N-GQDs) was explored for the first time toward hazardous heavy metal ions and they were found to be able to selectively detect cadmium ions (Cd(ii )). Abstract : In the present work, the sensing capability of nitrogen-doped graphene quantum dots (N-GQDs) was explored for the first time toward hazardous heavy metal ions and they were found to be able to selectively detect cadmium ions (Cd(ii )). Cd(ii ) is one of the hazardous heavy metal ions on the World Health Organization's list of 10 chemicals of major public health concern. The wide use of Cd(ii ) in industrial applications and its acute and chronic effects on living beings make the sensing of Cd(ii ) critical. The aromatic N-GQDs, synthesized here through a hydrothermal route using the single precursor polyaniline exhibited a 25- and 6-fold increase in the current response compared to that of a glassy carbon electrode (GCE) and GQD/GCE, respectively. It showed an excellent and exemplary selectivity toward Cd(ii ), with almost a nil current response for other interfering metal ions. The LOD value of 1.0 × 10 −5 ppb, i.e., in parts per trillion, by N-GQDs is the lowest value ever reported, which was 3–4 orders of magnitude lower than the previously reported values. The LOD was extended to the ultra-high sensitivity level of 1 × 10 −7 ppb, i.e., in parts per quadrillion, using a pre-reduction step. The LDR (0.001–112 000 ppb) and LOD values satisfactorily met the sensitivity requirement for detecting Cd(ii ) within the safe limit specified by the U.S. Environmental Protection Agency (EPA) of ≤5 ppb. The sensing performance of N-GQD/GCE was tested against real environmental samples spiked with Cd(ii ), such as groundwater, seawater, and wastewater, and was found to perform efficiently.